Public perception of climate change and its impact in Malaysia / Muhammad Huzaimi Ab Jalal and Mohamad Afiq Firdaus Mohd Zailani - Ab Jalal, Muhammad Huzaimi; Mohd Zailani, Mohamad Afiq Firdaus (2021)
Climate change knowledge is a growing topic that has piqued the curiosity of many people. This study is aiming to know what the effect and the impact of the climate change to the human is and how climate change can give impact to the human in Malaysia. The objective of this study is to examine the level of public perception and relationship between level education and gender on the impact of climate change. The place for this study is to be conducted in Malaysia and the study is conducted during the October 2020 until February 20222. This study employed a non-probability simple random sampling method because we are using online questionnaire by via social media and the sample size of the study will be 384 Malaysian citizens. The result of the study revealed three important findings. First, majority of the respondents were agreed that there is level of public perception on the impact of climate change with the highest mean (4.5865) and standard division (0.44969). Secondly, is to determine the relationship between level of education and public perception of climate change. The analysis reveals there is a significant and positive relationship between level of education and public perception (r =0.179**, p = 0.000). Thirdly is to determine the relationship between gender and public perception of climate change. The analysis reveals there is a significant and positive relationship between gender and public perception (r =0.099, p =0.053). Therefore, the work illustrates and provides some insights and builds on the literature in the area of organizational management from a developing country’s environment and public organization context.